2007
DOI: 10.1063/1.2738192
|View full text |Cite
|
Sign up to set email alerts
|

Photo-leakage-current characteristic of F incorporated hydrogenated amorphous silicon thin film transistor

Abstract: The photo-leakage-current (IPLC) characteristic of F incorporated a-Si:H thin film transistor (TFT) has been studied. The device activation energy (Ea) of a-Si:H(:F) TFTs is higher than those of typical a-Si:H TFTs, and resulted in the shift down of Fermi level in a-Si:H(:F). Experimental results show that the IPLC of a-Si:H(:F) TFTs is smaller than that of conventional a-Si:H TFTs in the density of states limited region, stemmed from the higher recombination centers present in a-Si:H(:F) material. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recently, Wang et al suggested that the incorporation of fluorine and chlorine into the amorphous-Si (a-Si) suppresses the leakage current by increasing the acceptor-like density of states. Increasing the acceptor-like density of state is a novel method to reduce the GIDL current due to its Fermi energy level shift; however, the fluorine and chlorine incorporation can damage and contaminate the pure intrinsic Si channel [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al suggested that the incorporation of fluorine and chlorine into the amorphous-Si (a-Si) suppresses the leakage current by increasing the acceptor-like density of states. Increasing the acceptor-like density of state is a novel method to reduce the GIDL current due to its Fermi energy level shift; however, the fluorine and chlorine incorporation can damage and contaminate the pure intrinsic Si channel [15].…”
Section: Introductionmentioning
confidence: 99%